DETIboot: a fast, wireless system to install operating systems on students laptops - Faneca, Carlos
This work presents a system conceived to deploy temporary Linux systems into an unlimited number of client hosts using a Wi-Fi source station (DETIboot server). The ultimate goal of this system is to provide a simultaneous and just-in-time installation of a custom Linux distribution on several tens of laptops for being used in classes or exams. DETIboot uses a server to endlessly broadcast a custom Linux distribution at maximum Wi-Fi transmission speed, using an ad-hoc network topology to reach all nearby target systems wishing to install it. To deal with packet losses and avoid feedback from the client hosts, we used Fountain Codes. With these codes, client hosts can start at any time the reception and the expected time for completing the download is mainly a function of the number of codewords (wireless frames) effectively received. Field tests were done to evaluate the performance of our system and in average it took around 69 seconds to download a custom Linux image (based on Slax) with a size of 225 MiB.